2008
DOI: 10.1177/0269881108093885
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions for the prevention of relapse in bipolar disorder: a systematic review of controlled trials

Abstract: We conducted a systematic review and meta-analysis of randomised and quasi-randomised controlled trials evaluating all clinically relevant pharmacological interventions for the prevention of relapse in people with bipolar disorder. Thirty-four trials were included in the review. Direct comparisons with placebo and with lithium were available for most drugs. In addition, there were direct comparisons of valproate vs. olanzapine, imipramine vs. lithium plus imipramine, olanzapine plus mood stabilisers vs. mood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 49 publications
0
38
0
1
Order By: Relevance
“…However, a recent systematic review still concluded that there was little evidence to support the efficacy of combination therapy despite its widespread use in Korean clinical practice. 7 Among types of MS, more clinical evidence (level A, full evidence from controlled studies) supports the use of lithium than that of valproate (level C, evidence from uncontrolled studies) in terms of efficacy in an enriched sample. 8 The Bipolar Affective Disorder: Lithium/Anticonvulsant Evaluation (BALANCE) study also showed that valproate monotherapy may have a lesser effect in preventing relapse rather than lithium + valproate and lithium monotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent systematic review still concluded that there was little evidence to support the efficacy of combination therapy despite its widespread use in Korean clinical practice. 7 Among types of MS, more clinical evidence (level A, full evidence from controlled studies) supports the use of lithium than that of valproate (level C, evidence from uncontrolled studies) in terms of efficacy in an enriched sample. 8 The Bipolar Affective Disorder: Lithium/Anticonvulsant Evaluation (BALANCE) study also showed that valproate monotherapy may have a lesser effect in preventing relapse rather than lithium + valproate and lithium monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…They were nearly all of the BP patients who had achieved clinical remission during the last 6 months and who had their medical records in the sites. Patients' prior episodes were identified as manic (199, 58.5%), hypomanic (33, 9.7%), mixed (25,7.4%), and depressive (70, 20.6%) ( Table 1).…”
Section: Demographic Data and Prescriptions At The Time Of Remissionmentioning
confidence: 99%
“…A systematic review of pharmacological interventions for the prevention of relapse in BD included 34 RCTs and quasi-RCTs, and concluded that lithium, olanzapine, and aripiprazole had significant effects in the prevention of manic relapses, as did divalproex, lamotrigine, and imipramine in the prevention of depressive symptoms (161). A meta-analysis of 20 RCTs (n = 5364) assessing the relative risk for relapse in patients with BD in remission confirmed the efficacy of lithium, divalproex, lamotrigine, and a number of atypical antipsychotic agents in preventing relapse to any episode versus placebo (162).…”
Section: Pharmacological Treatments For Maintenance Therapymentioning
confidence: 99%
“…Son yıllarda gerek Avrupa gerekse Amerika'da yeniden değerinin iade edilmeye çalışıl-dığı lityum ülkemizde en yaygın kullanılan duygudurum dengeleyicidir. [63] Duygudurum dengeleyici bir diğer antikonvulzan olan lamotrijin sadece depresif atakta %5'i aşan bir kullanım sergilemektedir. Çok uzun olmayan bir süre öncesine dek yaygın olarak kullandığımız karbamazepinin, her bir duygudurum döneminde ve iyilikte kullanımı, bu çalışmada çok çarpıcı bir şekilde gördüğümüz üzere %3'ü geçmemektedir.…”
Section: Tedaviunclassified